An Experimental Study on Compressive Strength of Concrete by Partial Replacement of Cement with SCBA - Sai Karthikeya, K.; Bharathi, L.; Sai Suresh, I.; Rahul Benrgee, CH.; Durga Rao, M. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The utilization of industrial and agricultural waste produced by industrial Processes have been the focus of waste reduction research for economic, environmental, and technical reasons. Sugar-cane bagasse is a fibrous waste-product of the sugar refining industry, along with ethanol vapor. This waste product (Sugar-cane Bagasse ash) is already causing serious environmental pollution, which calls for urgent ways of handling the waste. Bagasse ash mainly contains aluminum ion and silica. In this study, sugarcane Bagasse ash has been chemically and physically characterized, and partially replaced in the ratio of 0%, 5%, 10%, 15%, 20% and 25% by weight of cement in concrete. Fresh concrete tests like slump cone test were undertaken and as was well as hardened concrete test compressive strength at the age of 7 and 28 days was obtained. The result shows that the strength of concrete. In this present study SCBA has been partially replaced in the ratio of 0%, 10%, 15%, 20% and 25% by weight of cement in concrete. Concrete specimens were cured in normal water and NaCl solution comparison is made between them.